2022
DOI: 10.1093/jac/dkac159
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of antimicrobial resistance in Neisseria gonorrhoeae and Mycoplasma genitalium in sub-Saharan Africa

Abstract: Objectives Limited antimicrobial resistance (AMR) surveillance coupled with syndromic management of sexually transmitted infections (STIs) in sub-Saharan Africa (SSA) could be contributing to an increase in AMR in the region. This systematic review aimed to synthesize data on the prevalence of AMR in common STIs in SSA and identify some research gaps that exist. Methods We searched three electronic databases for studies publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Besides the high prevalence of MG, we also report on the presence of RAMs to macrolides and fluoroquinolones in MG among African MSM, which was previously mostly documented in high-resource settings [ 11 , 14 ]. The results found in our study population were different compared to MSM in high-resource settings.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Besides the high prevalence of MG, we also report on the presence of RAMs to macrolides and fluoroquinolones in MG among African MSM, which was previously mostly documented in high-resource settings [ 11 , 14 ]. The results found in our study population were different compared to MSM in high-resource settings.…”
Section: Discussionmentioning
confidence: 80%
“…Although MG resistance is frequently investigated in high-resource settings, data from the African region are scarce and mostly focus on women [ 14 ]. Studies from South Africa showed that the presence of RAMs to macrolides is rare to nonexistent, but RAMs to fluoroquinolones were more frequently detected [ 15–18 ].…”
mentioning
confidence: 99%
“…We found serovars D and G in this sample set, which were the two most common CT serovars in a 2012 study from nearby Guinea Bissau. (41) The low NG prevalence is reassuring, given NG's propensity to develop extensive drug resistance (42,43) resulting in it being on WHO's "high priority" list for new antibiotics. (44) MG is another pathogen where AMR is of increasing concern.…”
Section: Discussionmentioning
confidence: 99%
“…(44) MG is another pathogen where AMR is of increasing concern. (43,44) However, in a systematic review of mutations associated with macrolide and uoroquinolone resistance in MG, AMR data for the African region were only available from Kenya and South Africa. (45) Integrating AMR surveillance with prevalence and incidence monitoring would be valuable in this setting, particularly considering the amount of community-wide exposure to antimicrobials imparted by neglected disease mass drug administration campaigns in The Gambia and its neighbouring countries.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance is unexceptionally increasing in the field of obstetrics and gynecology. This includes drug-resistant Neisseria gonorrhea , Candida species, Mycoplasma genitalium , group B Streptococcus , and some Escherichia Coli isolates (ST131) [ 84 , 85 , 86 , 87 ]. Multiple antibiotic agents such as penicillin, cephalosporins, macrolides, fluoroquinolones, and trimethoprim/sulfamethoxazole are ineffective against these pathogens.…”
Section: Challenges In Clinical Management Of Cementioning
confidence: 99%